The problems faced by outpatients after gastrointestinal cancer chemotherapy and the methods they use to cope with these problems - Çiğdem Ökten; Tülin Bedük (Tehran University of Medical Sciences, 2017)
Background & Aim: Gastrointestinal cancer is one of the most common malignancies worldwide. Patients who undergo chemotherapy due to gastrointestinal cancer need to cope with the problems they face, as it will increase their quality of life and ability to take care of themselves. Therefore, it is important to determine patients' coping methods and their effects on nursing care. This study aims to explore the problems faced by outpatients after receiving chemotherapy due to gastrointestinal cancer and the methods they use to cope with such problems. Methods & Materials: This cross-sectional study was conducted in outpatient chemotherapy units of the Divisions of Medical Oncology at two medical school hospitals of a state university in Ankara, Turkey, between February and September 2011. A questionnaire developed by the authors in line with the literature to determine the patients' demographic characteristics, the problems they face, and their methods to cope with the adverse effects of chemotherapy and the Nightingale Symptom Assessment Scale were administered to 88 patients with gastrointestinal cancer admitted to the outpatient chemotherapy units to receive their third course of chemotherapy who met the inclusion criteria. Results: The patients mostly experienced nausea-vomiting (73.9%), malaise-fatigue (88.6%), loss of appetite (69.3%), and changes in taste and/or smell (54.5%) after chemotherapy. The methods most frequently used by the patients to cope with these problems were taking antiemetic drugs (46.6%), resting frequently/spending the day lying or sleeping (87.5%), and taking care of oral hygiene (27.3%). The general well-being was very good for 13.6%, good for 67%, fair for 15.9%, and poor for 3.4% of the patients. Of them, 40.9% received and 59.1% did not receive education on the adverse effects of chemotherapy. Conclusion: Individualized education programs on the adverse effects of therapy and the ways to cope with these effects should be provided to the patients before and during the therapy at the outpatient centers.